Desimination of technology for increasing the security of community-based citizens of Gawanan village, Colomadu using i-siskamling - Umi Salamah; Wiharto Wiharto; Ristu Saptono (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The residents of Gawanan Village, RT 02 and 04 RW 12 Colomadu, Karanganyar have almost the same characteristics: most of the residents work during the day and they are migrants. It gives security problems during the day, especially in an empty house and a long holiday. The vast area and the number of access roads, as well as proximity to the center of the crowd such as malls, factories, and warehouses, cause very inefficient when using security services during the day. Therefore, i-Siskamling which IP Camera Outdoor using internet access can be one solution to overcome these security problems. IP cameras are installed in strategic places. As a result, nine CCTV cameras with two controls (NVR) were installed with monitors at the two Partner locations. The results are very encouraging as seen from the absence of reports of theft in the two regions and the monitoring of several disturbing events in the community. In addition, community support was very evident with providing the electricity for the camera and access points and two additional CCTV cameras and accessories for the system.